Роль білінгвальної шкільної освіти у двомовному просторі Канади - Шийка, Юлія (Видавництво Львівської політехніки, 2015)
The article deals with the analysis of the scientificpedagogical literature and concerns the problems of bilingual education and its potential in the organization of secondary education. Bilingualism and organization of bilingual education is the object of scientific investigations of pedagogues, psychologists, sociologists etc. It is mentioned in the article that bilingual education forms language and cultural tolerance. Bilingual curriculums provide education in two or more languages and develop language and cultural apprehension.
Keywords: білінгвальна освіта; багатокультурність; державна мова; навчальні програми; корінне населення; національна меншина